Thyroxine Supplementation in Pregnant Women After Thyroidectomy for Thyroid Cancer and Neonatal Birth Weight - Ding, Zheng; Guo, Fei; Zhou, Yulai; Huang, Xiaoyi; Liu, Zhiwei; Fan, Jianxia (Frontiers in Endocrinology, 2021)
Patients are often supplemented sufficient dose of thyroxine to suppress thyroid stimulating hormone (TSH) after thyroidectomy for thyroid cancer. However, the influence of thyroxine supplementation on fetal growth in pregnant women after thyroidectomy for thyroid cancer is unclear. The aim of this study was to investigate the effect of TSH suppression on neonatal birth weight. This cohort study included 49896 pregnant women (278 cases with a history of thyroidectomy for thyroid cancer and 39363 control cases after exclusion). The thyroid parameters were examined in pregnant women and their newborns. The association between the maternal thyroid function index and neonatal birth weight and small for gestational age (SGA) was studied using regression analyses. In the levothyroxine (LT4) supplementation group, the free thyroxine (FT4) level was significantly higher in both early pregnancy (P < 0.001) and late pregnancy (P < 0.001) compared with the control group. Furthermore, the level of neonatal TSH (P = 0.032) and birth weight (P = 0.043) was significantly lower than that in the control group. The neonatal birth weight would significantly reduce (P= 0.003) when the maternal TSH level in early pregnancy was suppressed below 0.5mU/L. We also observed a significant inverse association between maternal FT4 level in early pregnancy and neonatal birth weight (P=0.028), especially for male newborns (P=0.036). In a word, after thyroidectomy for thyroid cancer, sufficient dose of thyroxine to suppress TSH in early pregnancy is significantly associated with reduced birth weight and thus needs to be closely monitored.